Suppose L represents the length and W represents the width. Relevant equations are

L*W = 40 m^2

W = 3*L

Substituting the second into the first, we get

L *(3*L) = 40 m^2

L^2 = (40/3) m^2 (divide by 3)

L = sqrt(40/3) m (take the square root)

L ~ 3.651 m

W = 3*L = sqrt(120) m ~ 10.954 m

L*W = 40 m^2

W = 3*L

Substituting the second into the first, we get

L *(3*L) = 40 m^2

L^2 = (40/3) m^2 (divide by 3)

L = sqrt(40/3) m (take the square root)

L ~ 3.651 m

W = 3*L = sqrt(120) m ~ 10.954 m